The Routledge Handbook on spaces of urban politics. - (:unkn) unknown (Routledge, 2018)
The Routledge Handbook on Spaces of Urban Politics provides a comprehensive statement and reference point for urban politics. The scope of this handbook s coverage and contributions engages with and reflects upon the most important, innovative and recent critical developments to the interdisciplinary field of urban politics, drawing upon a range of examples from within and across the Global North and Global South.
Keywords: Kommunalpolitik; Urbanität; Stadtentwicklung; Stadtplanung; Kommunalverwaltung; Wohnen; Wirtschaft; Umweltschutz; Naturschutz; Stadtverkehr; Segregation; Standortpolitik; Stadtentwicklungspolitik; Urbanisierung; Stadtökonomie; Stadtsystem; Steuerung; Governance; Räumliche Identität; Handbuch